Histopathological findings in the central nervous system of Rattus norvegicus infected with Angiostrongylus cantonensis - Solórzano-Alava, Luis (2017)
Rattus norvegicus is the definitive host of Angiostrongylus cantonensis. The aim of this study was to determine the type of macroscopic alterations and histopathological findings in the central nervous system (CNS) of R. norvegicus infected with A. cantonensis. A total of 35 rats were used. Among them, 23 rats from an animal facility were experimentally infected with L3 larvae and 5 remained as controls (not infected), and 7 rats that were captured in the city of Guayaquil, Ecuador, whose natural infection was confirmed in the laboratory. Seven out of 23 artificially infected rats showed changes in behavior (walking in circles) after 29 days post infection (dpi). Three of them were euthanized at 30-33 dpi and the other four at 48-105 dpi; also, all experimental rats and the seven captured rats were euthanized. The brains were dissected, weighed, perfused with 10% formalin and histologically processed. In the 30-33 dpi rats were found brain edema, gliosis, congestion, circular endothelial cell hyperplasia and development of L4-L5 larvae. In the brains after 48 dpi similar findings and dilation of blood vessels were observed. The average weight of brains positive to A. cantonensis at 30-33 and >48 dpi was 2.02 and 2.03 g respectively, while in the controls was 1.82 g. It is concluded that A. cantonensis causes lesions in the CNS of Rattus norvegicus.